The extent to al-Bayt University graduate students use the Internet in research, their attitudes towards it, and the obstacles to its use from their point of view - Al-Khalidi, Dalal Salama; Al-Khalidi, Hani Suleiman (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the reality of using Internet in scientific research, the researchers used the descriptive analytical method, and a questionnaire of (40) phrases divided into (3) fields as a tool that was distributed to a sample of (52) male and female students. The most prominent results of the study were the following: The tool’s general got a total average of (3.53 out of 5) with a grade (high), and at the level of domains, the domain of students’ attitudes towards the use of the Internet got the highest average (4.05) with a grade (high), then the field of the most important scientific methods of using the Internet with an average of (3.62) (high) and the third most important obstacles to using the Internet with an average of (2.92) (medium),Based on the results, the researchers recommended holding training courses to refine researchers' skills in using the Internet, and to overcome the difficulties that researchers face while using the Internet. Graduate Studies.
Keywords: Internet; scientific research; graduate students; Al al-Bayt University